Dissolved organic matter and terrestrial-lotic linkages in the central Amazon basin of Brazil - McClain, Michael E.; Richey, Jeffrey E.; Brandes, Jay A.; Pimentel, Tânia Pena (Global Biogeochemical Cycles, 1997)
We evaluate the hypothesis that decomposition and adsorption reactions operating in upland soils of headwater catchments control the concentration and composition of dissolved and fine particulate organic matter in rivers of the Amazon basin. In two contrasting first-order catchments characteristic of the central Amazon basin, we analyzed plant, litter, soil, groundwater, and stream water chemistry. Our results indicate that clear and persistent differences exist in the concentration and elemental composition of dissolved organic matter (DOM) in stream waters and groundwaters from the two catchments, due mainly to corresponding differences in soil texture and chemistry. Within the more oxide and clay rich Oxisols underlying terra firme forest, groundwater DOM concentrations were uniformly low (120 μMC) and C/N ratios averaged 10. Conversely, within the oxide and clay deficient Spodosols underlying campinarana forest, groundwater DOM concentrations were greatly elevated (3000 μMC), and C/N ratios averaged near 60. We found that, in the terra firme/Oxisol terrain, the majority of DOM contributions to the stream derived from the riparian zone, while in the campinarana/Spodosol terrain, upland groundwater contributions could account for the concentration and composition of DOM in the stream. The implications of our findings are that in the terra firme terrains which dominate the region, upland soil profiles are not the site of definitive processes which impart compositional signatures to organic matter carried by the largest rivers of the Amazon basin, as was hypothesized. Instead, we suggest that definitive reactions are focused primarily in the river corridor.
Keywords: Riparia